Genocide on settler frontiers : when hunter-gatherers and commercial stock farmers clash - Adhikari, Mohamed (War and genocide, 2015)
European colonial conquest included many instances of Indigenous peoples being exterminated. Cases where invading commercial stock farmers clashed with hunter-gatherers were particularly destructive, often resulting in a degree of dispossession and slaughter that destroyed the ability of these societies to reproduce themselves. The experience of aboriginal peoples in the settler colonies of southern Africa, Australia, North America, and Latin America bears this out. The frequency with which encounters of this kind resulted in the annihilation of forager societies raises the question of whether these conflicts were inherently genocidal, an issue not yet addressed by scholars in a systematic way.